Electromechanical properties of Bi(Mn1/2Ti1/2)O3 doped Pb0.94Sr0.05La0.01(Zr0.54Ti0.46)0.9975O3 materials - Nguyễn , Văn Thịnh; Đỗ, Viết Ơn; Lê, Đại Vương; Võ, Thanh Tùng (Hue University Journal of Science: Natural Science, 2025)
The solid-phase reaction technique was used to fabricate a Pb0.94Sr0.05La0.01(Zr0.54Ti0.46)0.9975O3 doped Bi(Mn1/2Ti1/2)O3 piezoelectric ceramic system. The material's structure and microstructure were examined by using scanning electron microscopy (SEM) and XRD analysis. The addition of Bi(Mn1/2Ti1/2)O3 to Pb0.94Sr0.05La0.01(Zr0.54Ti0.46)0.9975O3 contributes to the transition of the tetragonal phase to the rhombohedral phase; the average particle size decreases, while the mechanical quality coefficient Qm of the material increases. A product with a composition of 0.97 Pb0.94Sr0.05La0.01(Zr0.54Ti0.46)0.9975O3 – 0.03 Bi(Mn1/2Ti1/2)O3 has the characteristics of hard piezoelectric ceramic with the electromechanical coupling factor kp = 0.59; kt = 0.48; piezoelectric constant d33 = 446 pC/N; mechanical quality factor Qm = 774; phase transition temperature Tm = 265°C. This material exhibits properties comparable with commercial materials such as PZT4 and PZT8. This hard ceramic has the potential for use in power ultrasonic devices.